Neurobiological Effects of Transcranial Direct Current Stimulation: A Review - CAUMO, WOLNEI; Souza, Izabel C.; Torres, Iraci L.; Medeiros, Liciane; Souza, Andressa; Deitos, Alicia; Vidor, Liliane; Fregni, Felipe; Volz, Magdalena S. (Frontiers in Psychiatry, 2012)
Transcranial Direct Current Stimulation (tDCS) is a non-invasive brain stimulation technique that is affordable and easy to operate compared to other neuromodulation techniques. Anodal stimulation increases cortical excitability, while the cathodal stimulation decreases it. Although tDCS is a promising treatment approach for chronic pain as well as for neuropsychiatric diseases and other neurological disorders, several complex neurobiological mechanisms that are not well understood are involved in its effect. The purpose of this systematic review is to summarise the current knowledge regarding the neurobiological mechanisms involved in the effects of tDCS. The initial search resulted in 171 articles. After applying inclusion and exclusion criteria, we screened 56 full text papers to extract findings about the neurobiology of tDCS effects including investigation of cortical excitability parameters. Overall, these findings show that tDCS involves a cascade of events at the cellular and molecular levels. Moreover, tDCS involves glutamatergic, GABAergic, dopaminergic, serotonergic and cholinergic neurotransmitter function. However, further studies that aim to understand the basic and clinical neuroscience of tDCS are needed to improve our understanding on its entire mechanism of action and to also its impact in the clinical setting.